2015
DOI: 10.1002/anie.201507332
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Assembled Respiratory Chain that Catalyzes NADH Oxidation by Ubiquinone‐10 Cycling between Complex I and the Alternative Oxidase

Abstract: Complex I is a crucial respiratory enzyme that conserves the energy from NADH oxidation by ubiquinone‐10 (Q10) in proton transport across a membrane. Studies of its energy transduction mechanism are hindered by the extreme hydrophobicity of Q10, and they have so far relied on native membranes with many components or on hydrophilic Q10 analogues that partition into membranes and undergo side reactions. Herein, we present a self‐assembled system without these limitations: proteoliposomes containing mammalian com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 35 publications
5
50
1
Order By: Relevance
“…Kinetic studies using B. taurus complex I have revealed that the apparent second order rate constant for NADH binding (represented by k cat NADH /K M NADH , where k cat NADH is the (maximum) rate of NADH oxidation observed at saturating NADH concentration and K M is the Michaelis constant, equivalent to the NADH concentration required for half the maximum rate) is ~ 7.5 × 10 7 M − 1 s − 1 , approaching the diffusion-controlled limit, and that k cat NADH (which includes both reversible hydride transfer and NAD + dissociation) is greater than 15,000 s − 1 [14] , [19] . In comparison, the maximum rate of NADH:ubiquinone oxidation that has been observed is ~ 400 s − 1 [20] , [21] .…”
Section: Generating the Electrons For Ubiquinone Reductionmentioning
confidence: 92%
“…Kinetic studies using B. taurus complex I have revealed that the apparent second order rate constant for NADH binding (represented by k cat NADH /K M NADH , where k cat NADH is the (maximum) rate of NADH oxidation observed at saturating NADH concentration and K M is the Michaelis constant, equivalent to the NADH concentration required for half the maximum rate) is ~ 7.5 × 10 7 M − 1 s − 1 , approaching the diffusion-controlled limit, and that k cat NADH (which includes both reversible hydride transfer and NAD + dissociation) is greater than 15,000 s − 1 [14] , [19] . In comparison, the maximum rate of NADH:ubiquinone oxidation that has been observed is ~ 400 s − 1 [20] , [21] .…”
Section: Generating the Electrons For Ubiquinone Reductionmentioning
confidence: 92%
“…Compared with all the membrane mimetic systems explored in this review liposomes offer several unique advantages. First, the large size of liposomes allows for multi component systems (proteins, ligands and substrates) to be reconstituted [ 259 ]. Furthermore, the aqueous lumen can encapsulate soluble components allowing entire GPCR signalling pathways to be reconstituted, for example the M1 muscarinic receptor along with G q/11 βγ and phospholipase C in liposomes were induced to produce inositol triphosphate upon exposure of carbachol [ 260 ].…”
Section: Membrane Mimetic Systems For Structural and Functional Stmentioning
confidence: 99%
“…The addition of AOX provides a rapid secondary quinol oxidation route ( Fig. 1), such that NADH:O 2 turnover is capable of exceeding turnover by the canonical respiratory chain in an AOX-concentration dependent manner [24,25]. Thus, to prevent the substrate from becoming exhausted and ensure turnover during EPR sample preparation, AOX was titrated to a low level, at which the flux through the complex I-AOX pathway matched that through the canonical chain (Additional file 1, Figure S1).…”
Section: Smps and Aox-smps Are Well Coupled And Sustain A Proton-motimentioning
confidence: 99%
“…The alternative oxidase (AOX) from Trypanosoma brucei brucei was prepared and incorporated into SMP membranes as described previously [24,25]. A 100-μL sample of SMPs was incubated with the desired quantity of AOX (from a 3-5 mg/mL stock) on ice for at least 30 min.…”
Section: Preparation Of Aox-smps and Epr Samplesmentioning
confidence: 99%
See 1 more Smart Citation